The Role Of Polysemy In The Conceptual Integration Of Phraseological Units: A CrossLinguistic Approach (Czech Journal of Multidisciplinary Innovations, 2025)
This study explores the role of polysemy in the conceptual integration of phraseological units (PUs) in English, Russian, and Uzbek. The focus is on the polysemous word heart and its figurative uses across these three languages, examining how the meanings of heart contribute to the formation of idiomatic expressions. By analyzing a selection of idioms, the research demonstrates how polysemy enhances the richness of phraseological units and facilitates the blending of conceptual domains. The study finds that while the basic emotional and moral meanings of heart are shared across the languages, the specific cultural contexts shape the way these meanings are integrated in idiomatic expressions.